Wear resistance of composite electrolytic coatings - Skyba, M.Ye.; Stechyshyn, M.S.; Oleksandrenko, V.P.; Mashovets, N.S.; Bilyk, Yu.M. (Problems of Tribology, 2022)
The article analyzes the influence of composite electrolytic coatings (CEC) on the wear resistance of structural steels. The issues of matrix selection and various combinations in composite coatings of different chemical elements and compounds are considered. Coatings based on chromium, nickel, iron, copper, cobalt and others are widely used in industry, but nickel-based composite coatings are the most widely used. Nickel is widely used as a matrix for CEC, because it has an affinity for most particles used as the second phase and easily forms a coating with them. These coatings are used for corrosion protection, increase of physical and mechanical and chemical parameters, increase of hardness and wear resistance, restoration of the sizes, giving to a surface of self-lubricating properties. Nickel-based coatings with SiC filler of various fractions from size 100/80 μm to nanoparticles smaller than 50 nm were investigated on the basis of the established installation for CEC application. Thus, SiC powders with the following sizes were used in the works: less than 50 nm - nanoparticles; M5; 28/20; 50/40; 100/80 μm. In the studies performed, 0.01… 0.02 g/l sodium lauryl sulfate was additionally introduced into the electrolyte, which promotes the incorporation of SiC particles into the coating and improves the conditions for building the Nickel matrix. Amorphous boron powders of about 1 μm size were also added to the silicon carbides as a filler, which is explained by the possibility of boron and nickel interaction during the subsequent heat treatment of the coating and obtaining new structures (solid solutions, eutectic, dispersion-hard alloys). It is of practical interest to study the possibility of improving the physical and mechanical properties of nickel-based CEC by introducing metals capable of heat treatment, interact with the metal matrix to form solid substitution solutions and chemical compounds (solid phases of implementation) and determine tribotechnical characteristics of these coatings.